The sequence and organization of complete mitochondrial genome of the yellowfin tuna, Thunnus albacares (Bonnaterre, 1788). (2nd September 2016) - Pang, Jiaohui; Cheng, Qiqun; Sun, Dandan; Zhang, Heng; Jin, Shaofei
Abstract: Yellowfin tuna ( Thunnus albacares ) is one of the most important economic fishes around the world. In the present study, we determined the complete mitochondrial DNA sequence and organization of T. albacares . The entire mitochondrial genome is a circular-molecule of 16, 528 bp in length, which encodes 37 genes in all. These genes comprise 13 protein-coding genes (ATP6 and 8, COI-III, Cytb, ND1-6 and 4 L), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA genes (12S and 16S rRNAs). The complete mitochondrial genome sequence of T. albacares can provide basic information for the studies on molecular taxonomy and conservation genetics of teleost fishes.